The safety of intravitreal bevacizumab monotherapy in adult ophthalmic conditions: systematic review. Issue 7 (17th July 2014) - Poku, Edith; Rathbone, John; Wong, Ruth; Everson-Hock, Emma; Essat, Munira; Pandor, Abdullah; Wailoo, Allan
Abstract : Objectives: To assess the safety of intravitreal bevacizumab (IVB) as a monotherapy and to evaluate the relationship between quality of treatment and adverse events. Data sources: Cochrane Library, Ovid MEDLINE, MEDLINE in-process, Ovid EMBASE and Toxicology Literature Online (TOXLINE) from January 2009 to May 2012. Studies included in an earlier systematic review were also assessed for inclusion. Study eligibility criteria, participants and interventions: Randomised controlled trials (RCTs), controlled trials or observational studies including ≥10 participants reporting adverse events data following IVB monotherapy as a primary treatment in patients (aged 18 years or more) with any eye condition were included. Study appraisal and synthesis methods: Study selection was undertaken independently by a minimum of two reviewers using pre-defined criteria. Data abstraction and quality assessment were performed by one reviewer, and then checked by a second reviewer. Study quality was assessed for only RCTs in accordance to the Cochrane Risk of Bias Tool. Additional items relating to safety data were also assessed. Results were tabulated or meta-analysed as appropriate. Results: 22 RCTs and 67 observational studies were included. Only two RCTs reported valid safety data. Rates of serious adverse events following treatment were low. There was insufficient data to explore the relationship between the incidence of adverse events and quality of IVB injection. Limitations: A majority of relevant existing studies were characterised by small sample sizes, unclear diagnostic criteria and reporting of safety outcomes. Conclusions and implications of key findings: Available evidence demonstrates low rates of serious local and systemic adverse events following treatment. However, the role of IVB quality in the incidence of adverse events remains unclear. Robust evidence is needed to examine the relationship between the incidence of adverse events and variables such as injection techniques, pre-existing risk factors (eg, immunosuppression, cross-contamination) and quality of IVB treatment.